The Development of English Public Speaking Teaching Material Based on Interpersonal Intelligence for Fifth Semester Students of English Education Department of Universitas Muslim Nusantara Al-Washliyah - Aisyah; Asnawi (PT Inovasi Pratama Internasional, 2024)
This research aimed to describe the development, the validity, and the effectiveness of English public speaking based on interpersonal intelligence to overcome the difficulties. The method of this research was mixed qualitative and quantitative description research with test and questionnaire to collect the data. The object of this research was the 5A semester students at University of Muslim Nusantara Al-Washliyah. This research was carried out for 2 months. During this research the researcher found that public speaking material based on interpersonal intelligence can improve students’ public speaking ability in terms of self- confidence, mastering the topic, delivering the messages or ideas through verbal and non-verbal. The development material will make it easier for lecturer to teach public speaking and also be able to connect well between students and lecturer. Based on the research conducted, the result is the learning tools and the media developed are feasible to be used and applied in the learning process in the classroom with the final validation from material expert 87% and media expert 92,5%. Besides, the effectiveness of the learning method applied in this research shows the results of the calculation is 75% effective